Understanding the Promotion of Health Equity at the Local Level Requires Far More than Quantitative Analyses of Yes-No Survey Data: Comment on "Health Promotion at Local Level in Norway: The Use of Public Health Coordinators and Health Overviews to Promote Fair Distribution Among Social Groups" - Raphael, Dennis (Int J Health Policy Manag, 2018)
Health promotion is a complex activity that requires analytic methods that recognize the contested nature of it definition, the barriers and supports for such activities, and its embeddedness within the politics of distribution. In this commentary I critique a recent study of municipalities’ implementation of the Norwegian Public Health Act that employed analysis of "yes" or "no" responses from a large survey. I suggest the complexity of health promotion activities can be best captured through qualitative methods employing open-ended questions and thematic analysis of responses. To illustrate the limitations of the study, I provide details of how these methods were employed to study local public health unit (PHU) activity promoting health equity in Ontario, Canada.